Validation of a scale of measurement of service quality, image, customer satisfaction and loyalty in traditional trade - Veloso,Cláudia Miranda (2019)
The ability to create a satisfactory experience for the consumer in the retail industry remains in the hands of both the management and the retail staff to a considerable degree. The central purpose of this research is to validate an instrument for assessing the perceived quality of service, brand image, customer satisfaction and loyalty to traditional retail stores in Portugal. The findings of this research suggest that the 28 items of the scale can be grouped into four main dimensions and can be applied with confidence to Portuguese traditional retail as well. In addition, this survey can be regarded as a useful tool for traditional retail stores to help them to diagnose customer perceptions and, in a continuous search for customer satisfaction and loyalty to inquire about the drivers of these, moving towards the path of quality service and brand image, which is reflected in excellent organizational performance and higher profitability.